Morphological and process dynamics of the Lower Mississippi River - Harmar, Oliver Philip (2004)
This thesis uses data sets at a range of spatial and temporal scales to examine the geomorphological response of the Lower Mississippi River to engineering and management. During the twentieth century the geomorphology of the Lower Mississippi River has been transformed by a series of engineering modifications to improve flood control and aid navigation. These have included steepening of the longitudinal profile by removal of the most sinuous bends, fixing the river to a constant planform through extensive bank stabilisation, and regulating sediment movement through the channel system by dike field construction. Prior to these modifications, the Lower Mississippi River adjusted its planform morphology to satisfy large-scale flow resistance requirements. However, this mode of adjustment has been effectively removed and adjustments are now restricted to the long profile and cross-sectional form. Morphological analysis reveals that the river has responded to engineering intervention at two principal scales: by vertical changes in the elevation of the channel bed at the reach-scale; and by increasing large-scale bedform resistance at the sub-reach scale through longitudinal and cross-sectional adjustments. These mutual changes are consistent with the changes in water surface elevation in the post-modification period noted by Biedenharn and Watson (1997). However, analysis of morphological and process dynamics at shorter timescales shows that geomorphological response remains difficult to explain. This is because geomorphological behaviour at any scale, and in any location within an alluvial channel, is a product of complex spatially-distributed feedbacks between operating processes and multiple scales of channel morphology. This has general significance in terms of research design because detecting the complexity at each scale of adjustment, and forming linkages between scales of adjustment, is dependent on taking into account all possible degrees of freedom, and applying a range of complementary analytical techniques.